Celična terapija CAR-T - Cvetanoska, Maja (Placebo, 2023)
Chimeric antigen receptor T cell therapy, or CAR-T cell therapy for short, is a type of immunotherapy based on genetically modified proteins on the surface of T lymphocytes isolated from the patient's blood. Modifying the receptor proteins allows the T cells to specifically bind to target proteins on the surface of cancer cells. Binding to the target cells allows the T lymphocytes to be activated and the cancer cells to be destroyed. CAR-T therapy is particularly useful in the treatment of hematological malignancies. Despite the fact that this type of immunotherapy is a revolutionary tool for cancer treatment, there are a number of challenges that limit its use. Major obstacles include the absence or reduced expression of antigens on the cell surface due to the adaptation of cancer cells. Additional problems are the toxicity caused by excessive cytokine release and the immunosuppressive tumour environment, in the case of solid tumours, which at the same time is difficult for CAR-T cells to access. Modified natural killer cells are also a promising option and have several advantages over CAR-T.
Keywords: hematološke rakave bolezni; himerni antigenski receptor; Imunoterapija; limfociti T; rakave celice; terapija CAR-T; tumorsko mikrookolje